1978
DOI: 10.1152/jn.1978.41.3.821
|View full text |Cite
|
Sign up to set email alerts
|

Discharge properties of pontine reticulospinal neurons during sleep-waking cycle

Abstract: 1. Reticulospinal neurons were identified by antidromic invasion from spinal cord electrodes chronically implanted at C4 in cats. 2. Most of the neuronal population studied lay within the medial portion of the giant cell field from the anterior pontine and to the anterior medullary reticular formation (FTG). A few cells were found in the tegmental reticular nucleus (TRC) which has not previously been known to project to the spinal cord. 3. Extracellular action potentials from the neuronal somata of the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Meanwhile, the parallel development of basic neurophysiology focused on sleep itself and ignored consciousness [126][127][128][129][130][131] . This line of work was informed by the idea of neuronal clocks -first suggested by Thomas Graham-Brown, a pupil of Sherrington 132 -and famously evidenced by the studies of circadian rhythms 133 , which were found to be controlled in the suprachiasmatic nucleus of the hypothalamic brainstem 134 .…”
Section: Box 2 | Historical Backgroundmentioning
confidence: 99%
“…Meanwhile, the parallel development of basic neurophysiology focused on sleep itself and ignored consciousness [126][127][128][129][130][131] . This line of work was informed by the idea of neuronal clocks -first suggested by Thomas Graham-Brown, a pupil of Sherrington 132 -and famously evidenced by the studies of circadian rhythms 133 , which were found to be controlled in the suprachiasmatic nucleus of the hypothalamic brainstem 134 .…”
Section: Box 2 | Historical Backgroundmentioning
confidence: 99%
“…11,12 These cells activate premotor inhibitory interneurons in the region of the nucleus gigantocellularis which, in turn, discharge selectively during REM sleep. [13][14][15][16][17][18] They innervate motoneurons and promote their postsynaptic inhibition during REM sleep. 9,[17][18][19][20][21][22] Nevertheless, in 2008, Brooks and Peever 23 claimed that a "considerable controversy" exists regarding the neural mechanisms underlying REM sleep atonia (although they did not provide any references or data to support this claim).…”
Section: Over Forty Years Ago Investigators Hypoth-esized That the Reduction In The Contraction Of Hindlimb And Forelimb Muscles And Thementioning
confidence: 99%
“…Reticulospinal motor neurons, whose activity in waking is phase locked to somatic movement, are tonically excitable and fire phasically in REM sleep (Ito & McCarley, 1984; Steriade & McCarley, 1990, p. 337); owing to inhibition of spinal motor neurons, supraspinal motor commands are not enacted (Pompeiano, 1967). Small movements do override muscle paralysis (Pompeiano, 1967; Wyzinski, McCarley, & Hobson, 1978); some movement large enough to produce EEG artifact is characteristic (Muzet, Naitoh, Townsend, & Johnson, 1972). However, motor activation in REM sleep does not generate actual movement except in experimentally induced REM sleep without atonia (Jouvet & Delorme, 1965) and in human REM sleep behavior disorder (Schenck, Bundlie, Ettinger, & Mahowald, 1986).…”
Section: Three Models Of Dream Motionmentioning
confidence: 99%